Pro-poor tourism concept in the context of selected destinations in Ilocos region, Philippines / Ara Joyce Aya-Ay … [et al.] - Aya-Ay, Ara Joyce; Gabriel, Kathleen Joy; Guilatco, Deanne Pearl; Maglaya, Yulliam Shirlette; Mendoza, Martina Riah; Tacneng, Maria Agatha; Andalecio, Avi Ben P. (Universiti Teknologi Mara Selangor, 2020)
In recent years, poverty has been growing continuously throughout the parts of the world, most notably in developing countries like the Philippines. The purpose of this study is to assess the contributions of the tourism industry in selected destinations of Ilocos Region to successfully alleviate poverty and bring the country into inclusive growth. The assessment of poverty threshold is based on the economic benefits, non-cash livelihood benefits, tourism policies, government processes and participation of the community. Using a quantitative approach and Structural Equation Modeling, survey questionnaires were utilized to gather data from 250 household respondents in selected destinations of Ilocos Region, namely: Laoag in Ilocos Norte; Vigan in Ilocos Sur; San Fernando in La Union; and Alaminos in Pangasinan. In addition, interviews were conducted to the local government units, private sectors, and local community to support the collected information. Based on the results, the Local Government Unit’s tourism initiatives lead to Pro-Poor Tourism, which is perceived to contribute in alleviating impoverished households in the region of Ilocos.